Elevated Postmortem Vitreous Sodium and Chloride Level in a Salt Water Drowning Death During Self-Contained Underwater Breathing Apparatus Diving With Diving Mask in Place: Case Report. (September 2018) - Tse, Rexson; Garland, Jack; Kesha, Kilak; Morrow, Paul; Elstub, Hannah; Cala, Allan; Spark, Amy; Stables, Simon; Sage, Martin
Abstract : Abstract: Elevation of postmortem vitreous sodium and chloride (PMVSC) levels in salt water drowning (SWD) is hypothesized to result from electrolyte changes in blood from salt water inhalation/ingestion during drowning. After approximately 1 hour after death, electrolytes may diffuse into the vitreous humor via the eye coverings. This hypothesis was based on a study where bovine eyeballs were immersed in salt water. There is no human study that could confirm that SWD would result in an initial elevation of PMVSC with no effects from immersion. We present an SWD during self-contained underwater breathing apparatus diving in which the face mask remained in its correct position while the deceased was underwater. The face mask would have prevented the orbits from being in direct contact with salt water and therefore stopped any effects of immersion on PMVSC. The PMVSC was 294 mmol/L, above control levels, and the reported cut-off of 259 mmol/L for a diagnosis SWD. The elevated PMVSC would unlikely be owing to immersion but SWD. This case report supports the observation that during SWD PMVSC would initially increase from salt water inhalation and ingestion and not from immersion.